32.6: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/32.6#Ex1 32.6#Ex1] || [[Item:Q9239|<math>\deriv{q}{z} = \pderiv{\mathrm{H}}{p}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\deriv{q}{z} = \pderiv{\mathrm{H}}{p}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>diff(q, z) = diff(H, p)</syntaxhighlight> || <syntaxhighlight lang=mathematica>D[q, z] == D[H, p]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 300]
| [https://dlmf.nist.gov/32.6#Ex1 32.6#Ex1] || <math qid="Q9239">\deriv{q}{z} = \pderiv{\mathrm{H}}{p}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\deriv{q}{z} = \pderiv{\mathrm{H}}{p}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>diff(q, z) = diff(H, p)</syntaxhighlight> || <syntaxhighlight lang=mathematica>D[q, z] == D[H, p]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 300]
|-  
|-  
| [https://dlmf.nist.gov/32.6#Ex2 32.6#Ex2] || [[Item:Q9240|<math>\deriv{p}{z} = -\pderiv{\mathrm{H}}{q}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\deriv{p}{z} = -\pderiv{\mathrm{H}}{q}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>diff(p, z) = - diff(H, q)</syntaxhighlight> || <syntaxhighlight lang=mathematica>D[p, z] == - D[H, q]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 300]
| [https://dlmf.nist.gov/32.6#Ex2 32.6#Ex2] || <math qid="Q9240">\deriv{p}{z} = -\pderiv{\mathrm{H}}{q}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\deriv{p}{z} = -\pderiv{\mathrm{H}}{q}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>diff(p, z) = - diff(H, q)</syntaxhighlight> || <syntaxhighlight lang=mathematica>D[p, z] == - D[H, q]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 300]
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.6.E19 32.6.E19] || [[Item:Q9258|<math>(\alpha,\beta,\gamma,\delta) = \left(-2\kappa_{\infty}\theta_{\infty},2\kappa_{0}(\theta_{0}+1),\kappa_{\infty}^{2},-\kappa_{0}^{2}\right)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(\alpha,\beta,\gamma,\delta) = \left(-2\kappa_{\infty}\theta_{\infty},2\kappa_{0}(\theta_{0}+1),\kappa_{\infty}^{2},-\kappa_{0}^{2}\right)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma , delta) = (- 2*kappa[infinity]*theta[infinity], 2*kappa[0]*(theta[0]+ 1), (kappa[infinity])^(2), - (kappa[0])^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (- 2*Subscript[\[Kappa], Infinity]*Subscript[\[Theta], Infinity], 2*Subscript[\[Kappa], 0]*(Subscript[\[Theta], 0]+ 1), (Subscript[\[Kappa], Infinity])^(2), - (Subscript[\[Kappa], 0])^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.6.E19 32.6.E19] || <math qid="Q9258">(\alpha,\beta,\gamma,\delta) = \left(-2\kappa_{\infty}\theta_{\infty},2\kappa_{0}(\theta_{0}+1),\kappa_{\infty}^{2},-\kappa_{0}^{2}\right)</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(\alpha,\beta,\gamma,\delta) = \left(-2\kappa_{\infty}\theta_{\infty},2\kappa_{0}(\theta_{0}+1),\kappa_{\infty}^{2},-\kappa_{0}^{2}\right)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma , delta) = (- 2*kappa[infinity]*theta[infinity], 2*kappa[0]*(theta[0]+ 1), (kappa[infinity])^(2), - (kappa[0])^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (- 2*Subscript[\[Kappa], Infinity]*Subscript[\[Theta], Infinity], 2*Subscript[\[Kappa], 0]*(Subscript[\[Theta], 0]+ 1), (Subscript[\[Kappa], Infinity])^(2), - (Subscript[\[Kappa], 0])^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.6.E27 32.6.E27] || [[Item:Q9266|<math>(\alpha,\beta,\gamma,\delta) = \left(-4\eta_{\infty}\theta_{\infty},4\eta_{0}(\theta_{0}+1),4\eta_{\infty}^{2},-4\eta_{0}^{2}\right)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(\alpha,\beta,\gamma,\delta) = \left(-4\eta_{\infty}\theta_{\infty},4\eta_{0}(\theta_{0}+1),4\eta_{\infty}^{2},-4\eta_{0}^{2}\right)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma , delta) = (- 4*eta[infinity]*theta[infinity], 4*eta[0]*(theta[0]+ 1), 4*(eta[infinity])^(2), - 4*(eta[0])^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (- 4*Subscript[\[Eta], Infinity]*Subscript[\[Theta], Infinity], 4*Subscript[\[Eta], 0]*(Subscript[\[Theta], 0]+ 1), 4*(Subscript[\[Eta], Infinity])^(2), - 4*(Subscript[\[Eta], 0])^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.6.E27 32.6.E27] || <math qid="Q9266">(\alpha,\beta,\gamma,\delta) = \left(-4\eta_{\infty}\theta_{\infty},4\eta_{0}(\theta_{0}+1),4\eta_{\infty}^{2},-4\eta_{0}^{2}\right)</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(\alpha,\beta,\gamma,\delta) = \left(-4\eta_{\infty}\theta_{\infty},4\eta_{0}(\theta_{0}+1),4\eta_{\infty}^{2},-4\eta_{0}^{2}\right)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma , delta) = (- 4*eta[infinity]*theta[infinity], 4*eta[0]*(theta[0]+ 1), 4*(eta[infinity])^(2), - 4*(eta[0])^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (- 4*Subscript[\[Eta], Infinity]*Subscript[\[Theta], Infinity], 4*Subscript[\[Eta], 0]*(Subscript[\[Theta], 0]+ 1), 4*(Subscript[\[Eta], Infinity])^(2), - 4*(Subscript[\[Eta], 0])^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.6.E35 32.6.E35] || [[Item:Q9274|<math>(\alpha,\beta,\gamma,\delta) = \left(2\kappa_{\infty},\kappa_{0}(\theta-1),0,-\kappa_{0}^{2}\right)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(\alpha,\beta,\gamma,\delta) = \left(2\kappa_{\infty},\kappa_{0}(\theta-1),0,-\kappa_{0}^{2}\right)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma , delta) = (2*kappa[infinity], kappa[0]*(theta - 1), 0 , - (kappa[0])^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (2*Subscript[\[Kappa], Infinity], Subscript[\[Kappa], 0]*(\[Theta]- 1), 0 , - (Subscript[\[Kappa], 0])^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.6.E35 32.6.E35] || <math qid="Q9274">(\alpha,\beta,\gamma,\delta) = \left(2\kappa_{\infty},\kappa_{0}(\theta-1),0,-\kappa_{0}^{2}\right)</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(\alpha,\beta,\gamma,\delta) = \left(2\kappa_{\infty},\kappa_{0}(\theta-1),0,-\kappa_{0}^{2}\right)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma , delta) = (2*kappa[infinity], kappa[0]*(theta - 1), 0 , - (kappa[0])^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (2*Subscript[\[Kappa], Infinity], Subscript[\[Kappa], 0]*(\[Theta]- 1), 0 , - (Subscript[\[Kappa], 0])^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|}
|}
</div>
</div>

Latest revision as of 12:12, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
32.6#Ex1 d q d z = H p derivative 𝑞 𝑧 partial-derivative H 𝑝 {\displaystyle{\displaystyle\frac{\mathrm{d}q}{\mathrm{d}z}=\frac{\partial% \mathrm{H}}{\partial p}}}
\deriv{q}{z} = \pderiv{\mathrm{H}}{p}

diff(q, z) = diff(H, p)
D[q, z] == D[H, p]
Successful Successful - Successful [Tested: 300]
32.6#Ex2 d p d z = - H q derivative 𝑝 𝑧 partial-derivative H 𝑞 {\displaystyle{\displaystyle\frac{\mathrm{d}p}{\mathrm{d}z}=-\frac{\partial% \mathrm{H}}{\partial q}}}
\deriv{p}{z} = -\pderiv{\mathrm{H}}{q}

diff(p, z) = - diff(H, q)
D[p, z] == - D[H, q]
Successful Successful - Successful [Tested: 300]
32.6.E19 ( α , β , γ , δ ) = ( - 2 κ θ , 2 κ 0 ( θ 0 + 1 ) , κ 2 , - κ 0 2 ) 𝛼 𝛽 𝛾 𝛿 2 subscript 𝜅 subscript 𝜃 2 subscript 𝜅 0 subscript 𝜃 0 1 superscript subscript 𝜅 2 superscript subscript 𝜅 0 2 {\displaystyle{\displaystyle(\alpha,\beta,\gamma,\delta)=\left(-2\kappa_{% \infty}\theta_{\infty},2\kappa_{0}(\theta_{0}+1),\kappa_{\infty}^{2},-\kappa_{% 0}^{2}\right)}}
(\alpha,\beta,\gamma,\delta) = \left(-2\kappa_{\infty}\theta_{\infty},2\kappa_{0}(\theta_{0}+1),\kappa_{\infty}^{2},-\kappa_{0}^{2}\right)

(alpha , beta , gamma , delta) = (- 2*kappa[infinity]*theta[infinity], 2*kappa[0]*(theta[0]+ 1), (kappa[infinity])^(2), - (kappa[0])^(2))
(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (- 2*Subscript[\[Kappa], Infinity]*Subscript[\[Theta], Infinity], 2*Subscript[\[Kappa], 0]*(Subscript[\[Theta], 0]+ 1), (Subscript[\[Kappa], Infinity])^(2), - (Subscript[\[Kappa], 0])^(2))
Skipped - no semantic math Skipped - no semantic math - -
32.6.E27 ( α , β , γ , δ ) = ( - 4 η θ , 4 η 0 ( θ 0 + 1 ) , 4 η 2 , - 4 η 0 2 ) 𝛼 𝛽 𝛾 𝛿 4 subscript 𝜂 subscript 𝜃 4 subscript 𝜂 0 subscript 𝜃 0 1 4 superscript subscript 𝜂 2 4 superscript subscript 𝜂 0 2 {\displaystyle{\displaystyle(\alpha,\beta,\gamma,\delta)=\left(-4\eta_{\infty}% \theta_{\infty},4\eta_{0}(\theta_{0}+1),4\eta_{\infty}^{2},-4\eta_{0}^{2}% \right)}}
(\alpha,\beta,\gamma,\delta) = \left(-4\eta_{\infty}\theta_{\infty},4\eta_{0}(\theta_{0}+1),4\eta_{\infty}^{2},-4\eta_{0}^{2}\right)

(alpha , beta , gamma , delta) = (- 4*eta[infinity]*theta[infinity], 4*eta[0]*(theta[0]+ 1), 4*(eta[infinity])^(2), - 4*(eta[0])^(2))
(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (- 4*Subscript[\[Eta], Infinity]*Subscript[\[Theta], Infinity], 4*Subscript[\[Eta], 0]*(Subscript[\[Theta], 0]+ 1), 4*(Subscript[\[Eta], Infinity])^(2), - 4*(Subscript[\[Eta], 0])^(2))
Skipped - no semantic math Skipped - no semantic math - -
32.6.E35 ( α , β , γ , δ ) = ( 2 κ , κ 0 ( θ - 1 ) , 0 , - κ 0 2 ) 𝛼 𝛽 𝛾 𝛿 2 subscript 𝜅 subscript 𝜅 0 𝜃 1 0 superscript subscript 𝜅 0 2 {\displaystyle{\displaystyle(\alpha,\beta,\gamma,\delta)=\left(2\kappa_{\infty% },\kappa_{0}(\theta-1),0,-\kappa_{0}^{2}\right)}}
(\alpha,\beta,\gamma,\delta) = \left(2\kappa_{\infty},\kappa_{0}(\theta-1),0,-\kappa_{0}^{2}\right)

(alpha , beta , gamma , delta) = (2*kappa[infinity], kappa[0]*(theta - 1), 0 , - (kappa[0])^(2))
(\[Alpha], \[Beta], \[Gamma], \[Delta]) == (2*Subscript[\[Kappa], Infinity], Subscript[\[Kappa], 0]*(\[Theta]- 1), 0 , - (Subscript[\[Kappa], 0])^(2))
Skipped - no semantic math Skipped - no semantic math - -